2020
DOI: 10.3390/microorganisms8030343
|View full text |Cite
|
Sign up to set email alerts
|

Protein Aggregation is Associated with Acinetobacter baumannii Desiccation Tolerance

Abstract: Desiccation tolerance has been implicated as an important characteristic that potentiates the spread of the bacterial pathogen Acinetobacter baumannii on dry surfaces. Here we explore several factors influencing desiccation survival of A. baumannii. At the macroscale level, we find that desiccation tolerance is influenced by cell density and growth phase. A transcriptome analysis indicates that desiccation represents a unique state for A. baumannii compared to commonly studied growth phases and strongly influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 73 publications
(132 reference statements)
1
18
0
Order By: Relevance
“…In response to osmotic stress, A. baumannii also accumulates mannitol and glutamate; however, their contribution to desiccation resistance remains mostly unexplored [ 81 ]. To counteract the effects of oxidative stress, the expression of anti-oxidant enzymes, such as catalases KatE and KatG, superoxide dismutase, and glutathione peroxidase, is induced in desiccation-stressed A. baumannii [ 49 , 86 , 87 ]. A recent study by Farrow et al proved that the global BfmR regulator contributes to that desiccation tolerance [ 49 ].…”
Section: Mechanisms Protecting a Baumannii Agamentioning
confidence: 99%
See 2 more Smart Citations
“…In response to osmotic stress, A. baumannii also accumulates mannitol and glutamate; however, their contribution to desiccation resistance remains mostly unexplored [ 81 ]. To counteract the effects of oxidative stress, the expression of anti-oxidant enzymes, such as catalases KatE and KatG, superoxide dismutase, and glutathione peroxidase, is induced in desiccation-stressed A. baumannii [ 49 , 86 , 87 ]. A recent study by Farrow et al proved that the global BfmR regulator contributes to that desiccation tolerance [ 49 ].…”
Section: Mechanisms Protecting a Baumannii Agamentioning
confidence: 99%
“…The efficient solubilization of aggregated proteins requires the cooperation of the DnaK–DnaJ–GrpE system with ClpB (Hsp100), IbpA/B (the small Hsp family), or Hsp33, which is the primary chaperone redox-activated upon oxidative stress. Most of these chaperones were found to be upregulated in A. baumannii submitted to stresses that impair homeostasis: heat shock (DnaK, GroEL), oxidative stress (GrpE, DnaK, GroES, GroEL), antibiotic exposure (DnaK, GroEL), and desiccation (TF, GroES, GrpE, DnaJ, DnaK, ClpX, ClpB) [ 18 , 86 , 87 , 93 , 94 ]. Wang et al reported that the expression of more than 50 genes encoding proteins related to proteostasis, including chaperones and the Lon protease, was increased during desiccation [ 86 ].…”
Section: Protein Homeostasis In a Baumanniimentioning
confidence: 99%
See 1 more Smart Citation
“…For prokaryotes, this issue is insufficiently covered. Protein homeostasis of various model and extremophilic species of bacteria (E. coli, C. crescentus, Clostridium botulinum, Acine to bacter baumannii etc) is currently being actively studied [10,[26][27][28][29][30]34]. The emerging data on the study of these model bacteria show that accumulation of PAs is directly related to the impact of stressors and population "ageing".…”
Section: Protein Aggregation Is Provoked By Extrinsic and Intrinsic Smentioning
confidence: 99%
“…The emerging data on the study of these model bacteria show that accumulation of PAs is directly related to the impact of stressors and population "ageing". Increased protein aggregation is provoked by a heat shock, action of antibiotics (aminoglycosides) and antimicrobial peptides, depletion of the nutrient medium, oxidized stress, heavy metals, ultraviolet light, hydrostatic pressure, ionic strength, pH [24,32,[34][35][36] not provoke strong dispersion and lethality of the population [35,36]. Sublethal concentrations of aminoglycoside antibiotics such as kanamycin and streptomycin cause mRNA mistranslation, resulting in the creation of foldingdeficient protein species, which can induce aggregation [28].…”
Section: Protein Aggregation Is Provoked By Extrinsic and Intrinsic Smentioning
confidence: 99%